Variations in Seasonal Outbound Travel across the Business Cycles. (September 2018) - Smeral, Egon
This article analyses for the first time the asymmetric behavior in tourism demand by season across the business cycles based on time series and contributes herewith to a clear understanding of cyclical irregularities in tourism demand. For that reason, we study the outbound expenditures of four source markets per quarter, each understood as its own time series. In this new approach, we apply four types of demand functions showing distinct relationships only for the first, second, third, and fourth quarters. The results revealed strong evidence of asymmetric income elasticities in tourism demand by season across the business cycles. We emphasize coherently that the integration of psychological factors such as loss aversion and other quality-of-life aspects as well as economic factors like liquidity constraints, reluctant lending behavior of banks, precautionary saving, changing household behavior, and financial innovations delivers a new framework to explain asymmetric behavior in tourism demand.